Identification of subannual patterns in microbial community signatures from individual sedimentary laminae using a freeze‐coring approach. (22nd December 2015) - Harrison, B. K.; Myrbo, A.; Flood, B. E.; Bailey, J. V.
Abstract: Discrete biological community signatures were identified in individual sub‐annually deposited sedimentary laminae of anoxic lake sediments from two lakes in the Minneapolis–St. Paul (Minnesota, U.S.A.) urban area. Recognizing variation in microbial communities associated with discrete millimeter scale sedimentary horizons was made possible using a freeze‐coring method to recover bacterial DNA for amplicon iTag sequencing and Terminal Restriction Fragment Length Polymorphism analyses. Variation in 16S rRNA gene composition between laminae suggests that seasonal changes in cell transport from the water column impart a residual molecular signature on subsurface communities. Direct comparison of frozen‐in‐situ core samples to ambient temperature sediment indicates that freeze coring methodology imposes no significant bias on DNA‐based community fingerprints. This work further supports previous observations demonstrating the efficacy of freeze coring for high‐resolution analysis of microbial communities, but here it is applied to resolving molecular signatures derived from sedimentary laminae.